TINGKAT KEMAMPUAN LITERASI DIGITAL DI KALANGAN DIFABEL - Wulansari, Ayu; Winanto, Asis Riat; Nurhayati, Anna; Ekalawna, Akra Maratsa (Institut Agama Islam Negeri Salatiga, 2024)
The focus of this research is to determine the digital literacy ability of the blind disabled. Every citizen has the right to equality, easy access to information. This equality of rights is often constrained by the fact that the ease of access to information is not simply enjoyed by all people, as people with disabilities, especially those with disabilities, need special efforts and separate ways to improve their digital capabilities. Limitations do not prevent people with disabilities from enjoying and being able to access internet freely. Many digital literacy programs for the blind have been initiated by institutions, one of which is SLB-A Aisyiah, Ponorogo Regency. The purpose of this research is to determine the level of digital literacy ability of Aisyiah SLB-A students. The method used is descriptive quantitative with sampling using non-probability sampling, namely “a sampling technique that provides equal opportunities for each element (member) of the population. The population of this study was Aisyiah’s SLB-A students as many as 34 students at the junior high school level (SMP) and the senior high school level (SMA). The population is at the same time a sample or saturated sample. Analysis of the research data using statistics with the presentation of data through the formula mean and grand mean. “The mean is used to calculate the average value of the variables while the grand mean is used to calculate the total average. The main study is the assessment of digital literacy skills according to KOMINFO RI. The results showed that the digital literacy level of SLB-A students reached an average of 3.2 in the medium category. The first includes basic knowledge of conversational applications and social media which are categorized as high with an average result of 3.4. Second, is basic knowledge about information search engines, how to use and select data, the average is 3.25 in the medium category, the third position is basic knowledge about the digital landscape – internet and cyberspace, reaching 3.16 in the medium category, the average position is 3.16. the lowest average is basic knowledge about digital wallet applications, market stores, and digital transactions reaching 2.99 with less category